Signal configurations: Exploring set-theoretic relationships in angel investing - Edelman, Linda F.; Manolova, Tatiana S.; Brush, Candida G.; Chow, Clifton M. (Journal of Business Venturing, 2021)
Anchored in signaling theory, we use a configurational approach to examine how new ventures credibly communicate their underlying firm quality, using a unique dataset of 117 new ventures that sought investment from a prominent angel group located in the Northeastern United States. Unlike existing research, which employs econometric models to reflect one best solution, we use crisp-set qualitative comparative analysis (cs/QCA) to understand signal configurations during the angel investment decision-making process. Our findings suggest that there are multiple paths to our three outcomes, passed small group screening, passed large group presentation, and passed due diligence/invested, validating notions of equifinality. Signals are complementary and configurations differ by industry sector. We also find that effective signal configurations differ by stage of investment, thereby offering evidence of cognitive dual processing on the part of the angel investors. We contribute to the literature on signaling by linking our findings to recent work on signal interactions and by highlighting the configurational and temporal aspects of signaling in the angel investment context. Implications are discussed.